(untitled) (Journal of the College of Basic Education, 2023)
present work consist of a computational investigation aims at reveal the influence of narrowing or extending Grivet-Lenz model on its own projector properties. For this reason the well known formula of Grivet-Lenz model is raised to a power named in this work by “shape factor”. Projector properties and their related variables were determined for several values of the shape factor. Results have shown that as the shape factor value increases the magnetic field become more narrowing and its projector properties efficiency get worse. Accordingly to enhance the projector properties of Grivet model it should be extended over a wide axial interval.